Integrated Pest Management (IPM) in Cambodia - CGIAR Research Program on Rice (2021)
The USAID Integrated Pest Management (IPM) Innovation Lab and IRRI introduced an IPM system, which employs plastic barriers and wire traps, along with natural crop solutions that abate the use of synthetic chemicals.